2017
DOI: 10.1016/j.celrep.2017.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Citron Kinase Deficiency Leads to Chromosomal Instability and TP53-Sensitive Microcephaly

Abstract: SummaryMutations in citron (CIT), leading to loss or inactivation of the citron kinase protein (CITK), cause primary microcephaly in humans and rodents, associated with cytokinesis failure and apoptosis in neural progenitors. We show that CITK loss induces DNA damage accumulation and chromosomal instability in both mammals and Drosophila. CITK-deficient cells display “spontaneous” DNA damage, increased sensitivity to ionizing radiation, and defective recovery from radiation-induced DNA lesions. In CITK-deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(96 citation statements)
references
References 62 publications
6
77
1
Order By: Relevance
“…Fixed slices were imaged using a PL APO x40/1.2 NA oil immersion objective (Bianchi et al . ). All the images were analysed by using Fiji software.…”
Section: Methodsmentioning
confidence: 97%
“…Fixed slices were imaged using a PL APO x40/1.2 NA oil immersion objective (Bianchi et al . ). All the images were analysed by using Fiji software.…”
Section: Methodsmentioning
confidence: 97%
“…Finally, we have also shown that actively dividing and polyploid cancer cells are more susceptible to CIT-K depletion, suggesting that targeting CIT-K is a promising anti-cancer therapeutic approach for a wide range of cancers, especially those that are characterized by rapid cell proliferation and polyploidy ( . However, it is important to note that CIT-K loss can cause CIN owing to its involvement in DNA damage control and independently of its role in cytokinesis (Bianchi et al, 2017). This raises the possibility that the effects on cancer cells upon CIT-K depletion result from a combination of cytokinesis failure and increased DNA damage.…”
Section: Cit-k and Diseasementioning
confidence: 99%
“…Last, there is evidence that CIT-K has other roles besides in cell division. In addition to its recently described role in DNA damage (Bianchi et al, 2017), CIT-K has also been proposed to function in virus budding, organization of the Golgi complex and epigenetic gene silencing (Camera et al, 2003;Ding et al, 2016;Loomis et al, 2006;Sweeney et al, 2008) but, as yet, there are no major insights into its mechanisms of action in these processes.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Apoptosis of neuronal progenitors [76,77] Cell cycle and apoptosis (colon cancer, CC) [26] DNA damage, proliferation, cell senescence and apoptosis (medulloblastoma) [33] MCPH18 (WDFY3)…”
Section: Mcph17 (Cit)mentioning
confidence: 99%